A Review of Multi-phase Slag Refining for Dephosphorization in the Steelmaking Process - Lin, Wenhui; Jiao, Shuqiang; Zhou, Kaixiao; Sun, Jiankun; Feng, Xiaoming; Liu, Qing (Frontiers in Materials, 2020)
Dephosphorization has always been a challenging task in the steelmaking process. In the traditional studies, CaO-based steelmaking slag was usually treated as a homogeneous liquid phase to analyze the dephosphorization equilibrium between molten slag and hot metal (slag/metal). In fact, the slag shows a coexisting state of both liquid and solid at steelmaking temperature. In recent years, multi-phase slag refining has been proposed and proved to be an efficient technique to improve the utilization of solid lime and the dephosphorization efficiency in steelmaking practices. The present review focuses on hot issues for the multi-phase slag refining, including the dissolution of solid lime to the molten slag, the formation of 2CaO·SiO2 and phosphorus-rich solid solution of 2CaO·SiO2-3CaO·P2O5, as well as the phosphorus distribution ratio between the solid and liquid phases in the multi-phase slag. In addition to the discussion on thermal and kinetic factors of dephosphorization, the necessity of further research is proposed on the dissolution behavior of phosphorus-rich solid solution and phosphorus redistribution in the slag of high temperature, high basicity and high FeO in the final stage of converter steelmaking. Then, a more applicable dynamic model of dephosphorization could be expected considering the equilibrium not only between molten slag and liquid metal but also among the phases of the multi-phase slag in steelmaking process. Furthermore, the modelling work is beneficial for the fine control of the BOF process and the development of intelligent manufacturing in steelmaking industry.